Effect of low-dose radiation pre-irradiation on postoperative local chest wall recurrence of breast cancer—A retrospective study - Ruifang Zeng; Hanyu Wang; Xiaojun Cai; Junhao Lin; Pengfei Li; Shan Zeng; Aimin Li (PeerJ)
Purpose The purpose of this study was to determine the efficacy and safety of low-dose radiotherapy (LDR) for postoperative local chest wall recurrence of breast cancer. Methods The records of 52 patients with postoperative local chest wall recurrent breast cancer treated at our cancer center from January 2019 to December 2022. The t-test was used to compare the means of the LDR group and non LDR group. Categorical data were compared using the chi-square test. The Kaplan-Meier method were used to determine the factors associated the survival. Results Compared to patients who did not undergo LDR, patients in the LDR group showed a higher incidence of grade I side effects in their skin and soft tissue systems (p = 0.002), a significant reduction in grade II side effects (p < 0.05), and no grade III side effects. Compared with the non LDR group, the complete response rates were 42.3% vs. 38.5%, p = 0.777, the partial response rates were 53.8% vs. 50.0%, p = 0.781, and the objective relief rates were 96.2% vs. 88.5%, p = 0.833, respectively. The 3-year overall survival rate, local recurrence free survival rate, distant metastasis-free survival rate and disease-specific survival rate comparison between LDR group and non LDR group was 54.8% vs. 55.8%, p = 0.845 and 54.2% vs. 52.9%, p = 0.751, 67.9% vs. 51.9%, p = 0.097 and 39.2% vs. 49.6%, p = 0.993, respectively. Conclusion Compared with traditional radiotherapy, LDR pre-irradiation has better tolerance and efficacy in patients with local chest wall recurrence of breast cancer after operation.